Incidence, risk factors, and outcomes in electroencephalographic seizures after mechanical circulatory support: A systematic review and meta-analysis - Li, Qian; Shen, Jingjia; Lv, Hong; Liu, Yue; Chen, Yuye; Zhou, Chenghui; Shi, Jia (Frontiers in Cardiovascular Medicine, 2022)
Abstract： Purpose: To estimate the overall incidence, risk factors, and clinical outcomes of electroencephalographic (EEG) seizures for adults and children after mechanical circulatory support (MCS). Method and Measurements: This systematic review and meta-analysis was carried out in accordance with the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidance document. MEDLINE EMBASE and CENTRAL were investigated for relevant studies. The related information was retrieved by two independent reviewers and all analyses were conducted by STATA (version 16.0; Stata Corporation, College Station, TX). Result: Sixty studies including 36,191 adult and 55,475 pediatric patients with MCS were enrolled for evaluation. The study showed that the overall incidence of EEG seizures in adults was 2% (95%CI: 1%-3%), in which 1% (95%CI: 1%-2%) after CPB, and 3% (95%CI: 1%-6%) after ECMO. For pediatrics patients, the incidence of EEG seizures was 12% (95%CI: 11%-14%), among which 12% (9%-15%) after CPB and 13% (11%-15%) after ECMO. The major risk factors of EEG seizures after MCS in adults were redo surgery (coefficient=0.0436,p=0.044), and COPD (coefficient=0.0749,p=0.069). Additionally, the gestational week of CPB(coefficient=0.0544,p=0.080) and respiratory failure of ECMO (coefficient=-0.262,p=0.019) were also indicated to be associated with EEG seizures in pediatrics. Conclusion: EEG seizures after MCS were more common in pediatrics than in adults. Additionally, the incidence of EEG seizure after ECMO was higher than CPB both in adults and children. It is expected that appropriate measures should be taken to control modifiable risk factors, thus improving the prognosis and increasing the long-term survival rate of MCS patients. PROSPERO: CRD42021287288